ANALISIS BUDAYA KERJA MODEL ORGANIZATIONAL CULTURE ASSESSMENT INSTRUMENT (OCAI) DALAM PENCAPAIAN VISI PERUSAHAAN PADA PT. YODI INTIGUNA MANDIRI - BEKASI - Anwar, Yuli (Jurnal Ilmiah Binaniaga, 2013)
One of the factors that affect the performance of employees in a company is working culture, which is very closely related factor in improving employee performance, because the creation of a good work culture and supported by a collaboration with fellow employees, then it will achieve results that can improve the performance of work employee.OCAI (Organizational Culture Assessment Instrument) very useful in reflecting the direction where the company is categorized based on its culture to support the mission and purpose, and also to be able to identify the elements in the culture that can resist the mission and goals. And Vision shows a state or desired level of achievement or expected by the organization or company will be realized at a certain point of time in the future.The purpose of this study is to analysis of work culture model of Organizational Culture Assessment Instrument (OCAI) in achieving the company's vision on PT. Yodi Intiguna Mandiri. The population of this study were 25 employees at PT. Yodi Intiguna Independent located at the office.By measuring the achievement of the vision of the company by means of questionnaires to 25 respondents who terdiir of 6 groups, each group having 4 questions to measure the level of achievement of the vision of the company, can be seen in the following table. Clan Culture Vision : 27,5 Achievement : 30,2. Adhocracy Culture Vision : 21,7 Achievement : 24,6. Market Cilture Vision : 31,7 Achievement : 23,8 (Not Achieve). Hierarchy Culture Vision : 19,2 Achievement : 21,4. Of the four current work culture among the company's vision and achievement, there are three cultures is achieved by culture Clan, Hierarchy, and Adhocracy. And a culture that has not been achieved is the cultural Market.Keyword : OCAI (Organizational Culture Assessment  Instrument OCAI), Oganizational Culture, Vision.